Benign vascular lesions of the breast diagnosed by core needle biopsy do not require excision. Issue 5 (8th September 2017) - Sebastiano, Christopher; Gennaro, Lucas; Brogi, Edi; Morris, Elizabeth; Bowser, Zenica L; Antonescu, Cristina R; Pareja, Fresia; Brennan, Sandra; Murray, Melissa P
Abstract : Aims: Surgical excision of all benign vascular lesions of the breast identified by core needle biopsy has been recommended in the past to rule out a more serious lesion. In this study we investigated the clinical, radiological and pathological findings in patients diagnosed with a benign vascular lesion at our institution to assess whether excision may be spared for lesions without atypia. Methods and results: We searched the electronic medical record for patients with a vascular lesion of the breast diagnosed between 2000 and 2015. The study population consisted of 84 patients, 83 females and one male. The index diagnoses included 76 benign vascular lesions, five vascular lesions with cytological atypia and three angiosarcomas. A radiologist reviewed all pre‐ and post‐biopsy imaging studies; all cases had concordant radiological and pathological findings. Based on radiological and histological correlation, the vascular lesion accounted for the radiological target in 40 (48%) cases and was deemed an incidental finding in 44 (52%). Seven of 32 (22%) targeted and 10 of 44 (23%) incidental benign vascular lesions underwent surgical excision; there were no upgrades at excision. No recurrences or clinical events were observed in patients with a targeted or incidental benign vascular lesion with a median follow‐up of 39 months and 40.6 months, respectively. Conclusion: Our data suggest that benign vascular lesions diagnosed on core biopsy with concordant radiological and pathological findings do not warrant surgical excision.